Sprengel deformity: What is the functional outcome of conservative treatment versus surgical correction? - C. Antfang; A. Frommer; G. Gosheger; G. Toporowski; A. Laufer; J. D. Rölfing; R. Roedl; B. Vogt (Orphanet Journal of Rare Diseases)
Abstract Background Sprengel deformity is a rare congenital malformation of the scapula defined by malposition during embryonic development. Affected individuals have limited range of motion of the shoulder and torticollis. Surgical reconstruction is an option to treat patients with severe deformity and functional impairment. This retrospective single centre study evaluated 19 patients with 21 Sprengel deformities treated from 2016 to 2023. 11/19 patients had mild ROM limitations of the affected shoulder with a median abduction of 130° (interquartile range (IQR) 100–150) and were treated conservatively. 8/19 patients with severe Sprengel deformity and functional impairment underwent surgery (median age 6 years (IQR 4–6)). Surgery was conducted in a modified technique according to Green. The Cavendish and Rigault scores were employed to analyse function, cosmesis and the radiographic location of the scapula. Patient reported outcome measurements (EQ-5D-Y and the quick Disabilities of the Arm, Shoulder and Hand Questionnaire) were both administered at the latest follow-up. Results Patients treated conservatively had a median abduction of the affected arm of 130° (IQR 100–150) and a median Cavendish and Rigault score of both 2 (IQR 2–3 and 1.3-2, respectively). In the surgery group the median abduction improved by 45° (IQR 28–53) from 90° (IQR 90–90) preoperatively to 135° (IQR 120–140) 3 months postoperatively and was 110° (IQR 108–128) at latest follow-up. The median Cavendish score improved from 4 (IQR 2–4) to 1 (IQR 1–2). The median Rigault score was lowered from 3 (IQR 3–3) to 1 (IQR 1–2). The median time to return to daily life was 3 months (IQR 2.2–3.5). The median quickDASH score was 11.4 (IQR 7–31) in the surgical cohort and 9.1 (IQR 5–22) in the conservative cohort at median maximum follow-up of 62 months (IQR 22–118). The median EQ-VAS (Visual Analogue Scale) score was 81/100 (IQR 79–85/100) in the surgical cohort and 80/100 (IQR 59–95/100) in the non-surgical cohort. 4/8 patients treated surgically had fully reversible complications. Conclusions Surgical treatment of severe Sprengel deformity improves abduction of the affected shoulder and reduces disability in daily life. Patients with mild Sprengel deformity can have very good function of the shoulder and should not be considered for surgery.